Navigating the future of energy storage: insights into lithium-ion battery technologies - Chenchireddy, Kalagotla; Nagabushanam, Perattur; Dora, Radhika; Jagan, Vadthya; Sydu, Shabbier Ahmed; Manohar, Varikuppala (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Lithium-ion batteries are now considered essential technology for a wide range of contemporary applications due to the growing need for effective and sustainable energy storage solutions. The various lithium-ion battery chemicals that are covered in detail in this paper are lithium iron phosphate (LFP), lithium nickel manganese cobalt (NMC), lithium nickel cobalt aluminum oxide (NCA), lithium-ion manganese oxide (LMO), lithium-ion cobalt oxide (LCO), and lithium titanate oxide (LTO). Based on critical performance metrics such as energy density, life cycle, charge/discharge rates, cost, and operational temperature range, each kind is assessed. Additionally, the paper discusses the future potential of lithium-ion technologies, with a focus on advancements in energy density, safety, sustainability, and recycling. By assessing the strengths and limitations of various lithium-ion chemicals, this paper seeks to provide valuable insights into the rapidly evolving field of battery technology, highlighting their indispensable role in the transition to sustainable energy systems. Lithium ion batteries have the potential to significantly enhance the efficiency and dependability of energy storage systems in a variety of applications with further research and development.